Building Task-Based User Interfaces with ANSI/CEA-2018. - Rich, Charles (Computer (00189162), 2009)
The article provides information on the ANSI/CEA-2018 standard for user interfaces (UI). It facilitates a new kind of user interaction which directly addresses the device complexity problem. A shift in product design methodology is demanded by device complexity. JavaScript is used to implement communication between the task-based UI and the controlled devices in ANSI/CEA-2018.